Cohesive bond strength of marine aggregates and its role in fragmentation - Hayashi, Yasuhito; Wada, Shigeki; Seto, Mayumi; Adachi, Yasuhisa (Frontiers in Marine Science, 2023)
Marine aggregates are one of the main contributors to carbon sequestration in the deep sea through the gravitational settling of biogenic particles formed from the photosynthetic products of phytoplankton. The formation of large particles due to aggregation processes has been the focus of studies in the past, but recent findings on the spatio-temporal distribution of particles suggests that the fragmentation of aggregates plays an important role in aggregate dynamics. Here, we assessed the yield strength of aggregates derived from natural planktonic communities in order to analyze the cohesive bond strength and further understand fragmentation. The experimental approach was designed around the use of a Couette device, which produces a constant laminar shear flow of water. Aggregates were found to have a higher yield strength ( 289 ± 64 nN) during phases of nutrient depletion than those of mineral particles such as montmorillonite. Based on an estimated cohesive bond strength of 96 nN a numerical model to predict the temporal variation of aggregate size was created. The output of this model indicates that cohesive bond strength is a major determinant of the size of aggregates in motion. Our findings suggest that the dynamics of marine aggregates are greatly influenced by cohesive bond strength and the role in fragmentation.